Development of an experimental apparatus to observe ultrafast phenomena by tender X‐ray absorption spectroscopy at PAL‐XFEL. (12th December 2021) - Kim, Yujin; Nam, Daewoong; Ma, Rory; Kim, Sangsoo; Kim, Myung-jin; Kim, Jinhong; Eom, Intae; Lee, Jae Hyuk; Kim, Tae Kyu
Abstract : Tender X‐ray absorption spectroscopy was successfully performed with the newly developed experimental apparatus at PAL‐XFEL. Abstract : Understanding the ultrafast dynamics of molecules is of fundamental importance. Time‐resolved X‐ray absorption spectroscopy (TR‐XAS) is a powerful spectroscopic technique for unveiling the time‐dependent structural and electronic information of molecules that has been widely applied in various fields. Herein, the design and technical achievement of a newly developed experimental apparatus for TR‐XAS measurements in the tender X‐ray range with X‐ray free‐electron lasers (XFELs) at the Pohang Accelerator Laboratory XFEL (PAL‐XFEL) are described. Femtosecond TR‐XAS measurements were conducted at the Ru L 3 ‐edge of well known photosensitizer tris(bipyridine)ruthenium(II) chloride ([Ru(bpy)3 ] 2+ ) in water. The results indicate ultrafast photoinduced electron transfer from the Ru center to the ligand, which demonstrates that the newly designed setup is applicable for monitoring ultrafast reactions in the femtosecond domain.